Implementasi Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal di Rumah Potong Hewan Ruminansia Kecamatan Medan Deli - Syahputra, Teddy; Permata, Cahaya (Borneo : Journal of Islamic Studies, 2025)
A Ruminant Slaughterhouse is a facility for slaughtering animals to ensure that the meat distributed meets halal requirements. Halal certification ensures that animals are slaughtered by halal butchers in accordance with Islamic law. Therefore, to guarantee the halalness of the slaughtering process and the resulting products, slaughterhouses are required to obtain halal certification. This study aims to examine the implementation of Law Number 33 of 2014 on Halal Product Assurance at Ruminant Slaughterhouses in Medan Deli District. The research method used is empirical juridical, with data collection techniques including observation, interviews, and document studies. The research results indicate that the Halal Product Assurance Law has been implemented at Ruminant Slaughterhouses in Medan Deli District. This implementation is evidenced by the possession of halal certification and Juleha (Halal Butcher) certification issued by LPPOM MUI North Sumatra. However, the lack of transparency in the slaughtering process has led to public doubts regarding the halalness of both the slaughtering process and the resulting animal products. Therefore, increased transparency and supervision are needed to ensure that the implementation of the Halal Product Assurance Law can be carried out comprehensively and gain public trust.